Pengaruh Kualitas Produk dan Persepsi Harga terhadap Keputusan Pembelian Smartphone iPhone 16 di Kota Bandung dalam Perspektif Perilaku Keuangan Konsumen - Abdurachman, Fauzie; Herlina, Listi; Winar, Ilham (IKRAITH-EKONOMIKA, 2025)
This study aims to analyze the effect of price and product quality on the decision to purchase an iPhone 16 smartphone in Bandung. The study used a quantitative method with purposive sampling technique on 100 respondents. The data were analyzed using multiple linear regression analysis with SPSS 26. The results of the study show: (1) Price has a positive and significant effect on Purchase Decision (β = 0.450; sig = 0.001 < 0.05); (2) Product quality has a positive and significant effect on purchasing decisions with the most dominant influence (β = 0.421; beta = 0.570; sig = 0.000 < 0.05); (3) Price and Product Quality simultaneously have a significant effect on Purchase Decision (F = 89.871; sig = 0.000 < 0.05) with a contribution of 64.9% (R² = 0.649). From a consumer financial behavior perspective, the findings confirm that consumers of premium products apply the principle of perceived value, which integrates the elements of prestige pricing and product utility in rational purchasing decisions. Product quality is the main determinant of purchasing decisions, indicating that consumers prioritize long-term value over price alone. This study enriches consumer behavior research by integrating financial behavior perspectives in the context of purchasing premium technology products.